Changes in microstructure and mechanical properties of shales exposed to supercritical CO2 and brine. (December 2022) - Zhou, Dawei; Zhang, Guangqing; Huang, Zhongwei; Zhao, Jianlin; Wang, Linlin; Qiu, Renyi
Abstract: Shale is a source rock for hydrocarbon recovery that can be stimulated by CO2 -based fluids, as well as a caprock for CO2 geological sequestration due to its extremely low permeability. To examine the changes in microstructure and mechanical properties of shale exposed to supercritical CO2, the marine LMX gas shale and terrestrial Chang 7 oil shale from China, were treated with supercritical CO2 with temperature of 110 °C and pressure of 30 MPa for 30 days. The microstructural alterations were characterized by scanning electron microscopy (SEM) method and the pore size distribution changes were quantified by the low-field nuclear magnetic resonance (NMR) method. Finally, the cylindrical samples were loaded uniaxially to failure to measure the crack initiation stress and strength. The results show that new surface morphologies are created by microstructural changes due to the dissolution of calcite, precipitation of minerals and induced cracks. The reactions between supercritical CO2 and organic matter (OM) are much more significant in relatively low-mature Chang 7 shale in which massive oil in organic pores is extracted. Due to the cracks induced by the combined effects of brine and supercritical CO2, the macropores increase in the shale sample. Compared to the brine-saturated cases, the peak stress reduces 1.3% and 7.87%, Young's modulus decreases 30.80% and 18.31%, but the crack initiation stress increases 15.97% and 12.54% respectively, for the LMX and Chang 7 shales treated by supercritical CO2 -brine. Overall, the mechanical properties are significantly altered by the microstructural variations in shale induced by the strong interactions between CO2 -rich fluid and rock minerals.